OREGON SMALL BUSINESS OWNERS' DECISIONS CONCERNING EMPLOYEE RETIREMENT SAVINGS PLANS. (11th November 2018) - Neal, M; Dys, S; Hasworth, S
Abstract: In the U.S., the median retirement account balance is only $3, 000 for all working-age households and $12, 000 for near-retirement households. One reason is the relative lack of access to retirement savings programs at work, particularly among employees of small businesses. Thus, the OregonSaves program was created. Business owners set up a payroll deduction for employees, and employees are automatically enrolled, although participation is voluntary. Employees' Roth IRAs stay with them from job to job. To learn about small businesses owners' experiences and decisions concerning offering their employees retirement savings plans, a qualitative study, funded by AARP Oregon, was conducted. Three groups of small business owners (N=28 total) were interviewed: (a) those with no retirement savings plan for their employees, (b) those with a private plan, and (c) those participating in the new OregonSaves program. The findings from this study are presented, including similarities and differences in the three groups' responses with respect to their views of the severity of the problem and the impacts on individuals, society, and businesses, participants' perceptions of the importance of businesses offering some type of retirement savings program to their employees, the factors influencing small business owners' choices around this issue, and their experiences with retirement savings plans. Based on the findings and recognizing the limitations of the study, suggestions for changes in the OregonSaves program are presented.